Pingo Doce challenge : how to shift to a new positioning strategy without losing consumers’ loyalty? - Marques, Maria Margarida Crespo Silva (2020)
This thesis was developed based on a real company, Pingo Doce, a 200 years old Portuguese retailer. The goal was to understand its current positioning in the market and how a different positioning strategy could beneficiate the firm. More specifically, it focused on comprehending the event that happened on the 1st of May 2012, when the company shifted from an Every Day Low Price strategy to a continuous promotional cycle. Since then, Pingo Doce is offering promotions to its consumers, immediate or delayed, but without extracting key information about its consumers which enables the company to build a strong customer’s data base and to tailor their offers. The purpose was to identify who Pingo Doce’s consumers are, what do they value and how the company could obtain relevant data about them to have a well-defined Customer Relationship Management (CRM) strategy. This strategy must be incorporated within the consumers’ needs in order to change the firm’s current price positioning to a more sustainable one in the long-term.